The Influence Of Corporate Image And Social Media Marketing On The Purchase Decision Of Pt. Yusuf Mamlaka Mubarokah Products In Bojonegoro - Muhammad Adrian Reza Wahyuaji; Sugeng Purwanto (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the extent to which corporate image and social media marketing influence purchasing decisions at PT. Yusuf Mamlaka Mubarokah, an agribusiness company based in Bojonegoro Regency. Employing a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis, the research involved 108 active consumer respondents. The findings indicate that both corporate image and social media marketing have a positive and significant effect on purchasing decisions. Corporate image is shaped by elements such as impression, trust, and attitude, while social media marketing is supported by dimensions of content, audience engagement, and digital interaction. These results highlight the importance of optimizing corporate communication strategies and strengthening digital promotion efforts to enhance consumer loyalty and purchase intention.